Reasons for nutritional supplements i use by physical activity practioners of Antônio Prado-RS - Sabrina Susin; Juliana Zortéa; Bruna Nicoletto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
Objective: To verify the reason for the use of nutritional supplements among gym goers in Antônio Prado-RS. Cross-sectional study evaluating all 222 physical activity practitioners attending the five gyms in the city using nutritional supplements. Whey protein was the most used supplement (40.5%). The frequency of whey protein, maltodextrin, creatine, caffeine, BCAA and mass gainer was higher, while collagen and omega-3 was lower in those looking for hypertrophy. For weight loss, there was a higher use of whey protein, maltodextrin, caffeine and BCAA. For well-being, collagen use was higher than whey protein, creatine and BCAA. In conclusion, proteins were more commonly used between those looking for hypertrophy and weight loss, while collagen was related to well-being.